PEDAGOGICAL AND COMMUNICATIVE SKILLS IN TEACHER'S ACTIVITY - Tsagaraeva Olga Batirbekovna (Scholars Digest Publishing, 2023)
This article highlights the significance of pedagogical and communicative skills in a teacher's activity and their impact on effective teaching and learning. It explores the pedagogical skills involved in lesson planning, classroom management, assessment, differentiation, and individualization. Additionally, it discusses the communicative skills of verbal and nonverbal communication, active listening, questioning, and facilitation. The integration of these skills is emphasized as a means to foster student engagement, promote effective knowledge transfer, establish positive relationships, and address individual needs. The article underscores the importance of continual professional development and reflective practice in refining and adapting these skills to meet the evolving needs of students and the educational landscape.
Keywords: pedagogical skills, communicative skills, effective teaching, learning environment, student-teacher interaction, knowledge transfer, engagement, differentiation, assessment, classroom management, communication techniques.